A systematic review and meta-analysis of survivorship and wear rates of metal and ceramic heads articulating with polyethylene liners in total hip arthroplasty. Issue 6 (November 2020) - Gosling, Oliver B; Ferreri, Thomas G; Khoshbin, Amir; Whitehouse, Michael R; Atrey, Amit
Background: The major joint registries report better survivorship for ceramic on polyethylene over metal on polyethylene bearings in total hip arthroplasty and it is generally accepted that this is due to a lower polyethylene wear rate. We used evidence synthesis to compare survivorship, polyethylene wear rates and metal ion levels for metal-on-polyethylene (MoP) and ceramic-on-polyethylene (CoP) bearings. If wear rates are not dissimilar in vivo this difference in revision rate may have another cause. Modular junctions are a potential source of corrosion and it is postulated that this may result in higher revision rates. Methods: We performed a systematic review and meta-analysis comparing the survivorship of MoP and CoP bearings. Odds ratio (95% CI) of revision was calculated. Mean difference (MD) and 95% confidence intervals (CI) were used to compare secondary outcomes of polyethylene wear and metal ion levels. Meta-analysis was performed with a Mantel-Haenszel Random-Effects Model. Results: 6 randomised controlled trials were included. There was no statistically significant difference between MoP and CoP revision rate (OR 1.04; 95% CI, 0.37–2.90, I 2 = 0%, p = 0.94), linear bearing wear (MD 0.00 mm; 95% CI, −0.05 –0.05, I 2 = 98%, p = 0.90), nor volumetric bearing wear (MD 33.57 mm 3 ; 95% CI, −215.56–282.70, I 2 = 98%, p = 0.79). No studies evaluated metal ion levels. Conclusions: We found no evidence of a difference in revision rates nor linear and volumetric wear between MoP and CoP bearings in the randomised controlled trials currently available. Our study therefore does not advocate the additional cost associated with the use of ceramic heads in combination with polyethylene bearings in order to minimise revision rates. This contrasts the findings of in vitro studies and the major joint registries.